pH Role in Green Synthesis of Silver Nanoparticles Using Extract of various Plant Parts: A review - Alfaid, Mofida M.; Elraies, Samia Sallah Eldien; Omar, Abdounasser Albasher (Scientific Journal for Faculty of Science-Sirte University, 2024)
<thead> Synthesizing silver nanoparticles (AgNPs) from extracts of various plant parts and of agricultural waste is strongly affected by pH. These green synthesis methods cconsidered simple, cost effective, ecofriendly, and biologically effective. This brief review aimed to survey the role of pH in the green synthesis of AgNPs using those media, with a focus on its effect on AgNPs morphology and size. This review article revealed that the alkaline pH (9 - 10) is the optimum condition for synthesizing more stable and tiny uniform AgNPs. In addition, according to the reviewed articles, the spherical shape is the most dominant shape of these articles in the basic medium and the size of these particles decreases at elevated pH values and ranged from 5-40 nm. </thead>